The Effect of Time Variations in the Hot Dipping Alumunizing Coating Stainless Steel 304 Process on Material Characteristics and Thermal Conductivity - Ferry Setiawan (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2022)
This study aims to determine the effect of time on the hot dipping process of aluminizing coating stainless steel 304 material on the characteristics of the tensile test material, hardness test, thickness test and the value of thermal conductivity. The application of this material is on a Cessna 150 aircraft which is used in the firewall section. Hot dipping alumunizing coating is a process to add a layer on the surface of a material, by immersing the main metal into a bath containing the molten coating metal, the melting of aluminum metal in this study was carried out at a temperature of 700 oC. The time that was varied in the hot dipping aluminizing coating process for stainless steel 304 material was 2 minutes, 4 minutes and 6 minutes. Based on the research that was done, the best results were obtained on each material test, namely; Tensile test on a 4 minute immersion time variation with a tensile stress value of 232 Mpa, Hardness test on a 4 minute immersion time variation with a Vickers Hardness value of 90 kgf/mm2, Thickness test on a 6 minute immersion time variation with a layer thickness of 130.48 m, Conductivity test thermal variation at 6 minutes of immersion time with a value of K 33.70 W/m K. From the results of the study, it was found that the weakness of the hot dipping alumunizing coating process was the result of an uneven aluminum coating so that there is potential for deviation in the test results.